PENGARUH LAPISAN HIDROFOBIK PADA PERMUKAAN ISOLATOR KERAMIK TIPE POST TERHADAP TINGKAT ARUS BOCOR PADA KONDISI KERING DAN BASAH - Wijaya, Rizki Adi; Dhofir, Moch.; Hasanah, Rini Nur (Jurnal Mahasiswa TEUB, 2024)
In this research will be explained about the effect of silicon rubber coating on ceramic insulators type post on leak current levels in dry and wet conditions. The research method used is to collect data through testing leakage current and contact angle at the High Voltage Laboratory, Department of Electrical Engineering, Faculty of Engineering, Brawijaya University and simulating the electric field distribution in Ceramic Insulator Type Post with FEMM 4.2 software. The tests were conducted using high voltage AC with variations of voltage tests of 4.8,12,16,20, and 25 kV. The results obtained in this research are that the largest electric field is near the voltage area. Then we get a contact angle of more than 90° or is hydrophobic when coated with silicon rubber, whereas the surface of the insulator which is not coated with silicone rubber has a contact angle of less than 30° or is hydrophilic, and there is an effect of the silicon rubber layer on the leakage current level, namely the greater the wetting discharge value and test voltage, the greater the leakage current value and the greater the surface resistance value. and electrical power losses Keywords: ceramic insulator,post type, contact angle, leakage current, field intensity, hydrophobic